Decoding the Clinical Significance of Immunoglobulin G4 in Rheumatoid Arthritis - Tan, Li Fen; Sakthiswary, Rajalingham; Veshaaliini, Uma Rajeswaran; Shaharir, Syahrul Sazliyana; Wahab, Asrul Abdul; Aziz, Suraya; Sutan, Rosnah (Journal of clinical medicine, 2023)
Immunoglobulin (Ig) G4 accounts for 4–6% of the total IgG in a healthy human. Several evidence-based studies have suggested that the level of IgG4 is significantly elevated in autoimmune diseases, including rheumatoid arthritis (RA). The clinical significance of IgG4 in RA with regard to disease activity, severity, and treatment response remains elusive. We consecutively recruited 174 patients with RA from our rheumatology clinic. All subjects were assessed for their disease activity based on DAS28, radiographic joint damage based on the Modified Sharp Score (MSS), the functional capacity based on the Health Assessment Questionnaire –Disability Index (HAQ-DI), and treatment responsiveness using the European League Against Rheumatism (EULAR) response criteria. The serum IgG4 of the recruited subjects was measured via the ELISA test. The mean serum IgG4 level was 60.23 ± 30.08 mg/dL. We found that serum IgG4 had significant positive correlations with disease activity (r = 0.406; p < 0.001), ESR (r = 0.155; p = 0.041), CRP (r = 0.269; p < 0.001), joint damage (r = 0.195; p = 0.012) and functional disability (r = 0.909; p < 0.001). Subjects with elevated IgG4 (IgG4 > 86 mg/dL) had significantly higher ESR, CRP, HAQ-DI, and DAS 28 and a poorer treatment response compared to the group with non-elevated IgG4. After multivariate analysis, only HAQ-DI (OR = 4.229, 95% CI 1.302, 15.751, p = 0.018) and DAS28 (OR = 3.743, 95% CI 1.062, 13.193, p = 0.040) remained significantly associated with elevated serum IgG4. The preliminary findings of this study could suggest serum IgG4 to be a potential biomarker of disease activity and functional disability in RA.